PENENTUAN TOTAL HARGA POKOK PRODUKSI TEPUNG KELAPA PADA PT. PUTRA KARANGETANG DESA POPONTOLEN, KECAMATAN TUMPAAN, SULAWESI UTARA - Tengku M.A Aboka; Agnes E. Loho; Ribka M. Kumaat (AGRI-SOSIOEKONOMI, 2016)
North Sulawesi is one of the biggest coconut producer in Indonesia . This situation provides an opportunity for PT .Putra Karangetang processing of coconuts into deciccated coconut . To determine the selling price of this industry, it is necessary to determine the cost of production . This study uses a case study by using primary and secondary data . The data was analyzed by the method of full costing and variable costing. The results showed that the cost of production of each kilogram of desiccated coconut by the company amounted to Rp 18.067,17 while using the full costing is Rp 18.155.31 and variable costing is Rp 17.651.53 .*ael*